Aplicação web para logística na captação de leite - Sganderla, Eduardo (2018)
As the complexity of logistics problems increases in agribusiness, the need to study and use new approaches to improve this process raises. The development of new technological tools has helped the logistics chain process, such as the transportation cycle, which uses computerized systems aiming cost reduction by using routing optimization. Although software for routing has many benefits, the cost of implementation can make it unfeasible for small businesses, especially those that require a customized system for a specific area (milk collection, for example). In this context, the objective of this work was to develop and make available, free of charge, a computational tool in a web environment, that allows create optimized routes for milk collection. In the development process, we used statistical methods suggested in the literature (Dijkstra Algorithm -minimum cost path problem). The software was tested with real data from an agroindustry located in the western region of the state of Paraná, which collects and processes milk in three cities. The results showed that the use of the software allowed the creation of optimized routes based on variables (physical characteristics) of roads and vehicles. The report function, added to the system, makes it possible to evaluate the geographical distribution of each rural property crossing its respective production and route, allowing the user to identify possible causes of inefficiency and costs. Because it is installed on a server with on-demand resources, the software, in a functional point of view, has satisfactory performance, and can be accessed from any browser.